ANALISIS MODEL PEMBELAJARAN BLENDED LEARNING DITINJAU DARI HASIL BELAJAR SISWA PADA SEKOLAH DASAR DI BANJARBARU - Nayla Amalia (PROCEEDING UMSURABAYA, 2022)
Learning with the blended learning model is a learning activity by combining face-to-face learning with virtual learning that is integrated with technology. The purpose of this study is to analyze the blended learning model in terms of student learning outcomes in elementary schools in Banjarbaru and what factors support and hinder the blended learning learning model. This type of research is a field research (field research) with a qualitative approach. The research subjects in this study were PAI teachers. The object of this research is the analysis of the blended learning model in terms of student learning outcomes. Data collection techniques in this study using observation, interviews and documentation. The results of this study indicate that the application of the blended learning model is less effective in terms of student learning outcomes who experience a decline. This is due to the lack of parental roles during the implementation of learning, whether it is due to infrastructure, learning time and parents' educational background.Â Keywords: blended learning model; student learning outcomes